Optimalisasi Sistem Akuntansi Pendapatan untuk Mendukung Efisiensi Pengelolaan Keuangan dalam Pengambilan Keputusan Manajerial pada Hotel Front One Budget Malang - Ashari, Muhammad Hasyim Ashari; Aldian Fiki Bawenda (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Efficient financial management is crucial for the operational sustainability of hotels, including in terms of revenue. Front One Budget Hotel Malang faces challenges in its revenue accounting system, which has not been optimized. This community service activity aims to develop and optimize the revenue accounting system to support financial management efficiency and managerial decision-making. The method used is Community Development, where the service team collaborates with the hotel management to analyze and design a more effective system. Training and mentoring are provided to staff to implement the new system. The results of the activity show improvements in revenue recording accuracy, financial process efficiency, and more accurate data-driven decision-making. The hotel’s financial management becomes more transparent and effective, having a positive impact on the hotel's managerial performance.